Mediastinal gray zone lymphoma in a pregnant woman presenting with cardiac tamponade - Azin Alizadehasl; Kamran Roudini; Mahshid Hesami; Farid kosari; Hamid Reza Pouraliakbar; Mina Mohseni; Negar Dokhani (Cardio-Oncology, 2023)
Abstract Background Mediastinal gray zone lymphoma is a newly recognized rare B cell neoplasm, which is challenging in diagnosis and treatment. Case presentation In the current study, we aimed to report a 25-year-old pregnant woman at 25 weeks of gestation who presented with chronic cough and progressive shortness of breath, hypotension, tachycardia, and tachypnea. A large circumferential pericardial effusion with compressive effect on the right atrium and right ventricle and a large extracardiac mass with external pressure to mediastinal structures were seen on trans thoracic echocardiography. The emergency pericardiocentesis was performed with the diagnosis of cardiac tamponade. Also, CMR revealed a huge heterogeneous anterior mediastinal mass, and the pathology and the immunohistochemistry of the mass biopsy revealed gray zone lymphoma with positive CD3, CD20, CD30, CD45, PAX5, and negative CD15 expression. Three courses of chemotherapy with the CHOP regimen were performed with an acceptable response every three weeks before delivery. A caesarian section was performed at 37 weeks without any problem for the patient and fetus, and chemotherapy will be started three weeks after delivery. Conclusion Cardiac tamponade as an emergency condition occurred in this pregnant patient by malignant pericardial effusion and mediastinal mass pressure. Accurate diagnosis and on time interventions caused a significant improvement and a successful delivery.